Environmental carrying capacity review in cengklik reservoir - asmaranto, Runi; Suryono, Antonius (International Journal of Engineering and Technology, 2018)
Reservoir is a body of water that is formed or modified by humans by damming the river for a particular purpose and can be controlled in its use. Cengklik Reservoir besides its main function as irrigation facilities covering an area of 1,578 ha, is also used for tourism activities and aquaculture. However, on December 29th, 2015 many of the fish in the reservoir died. Cultivated fish died suspected to be caused poisoning by reservoir water that contaminated with waste. This study aims to examine the contamination conditions of the current Cengklik Reservoir and how the reservoir zonation for carrying capacity of the growing floating net cage cultivation. This study was conducted using descriptive analysis method based on the results of qualitative and quantitative tests of primary data in the form of water quality of Cengklik Reservoir. The method of research conducted through 4 stages namely preparation, data collection, data analysis, analysis of results discussion and conclusion. It is expected that the results of this study can be used as a review of Reservoir zonation management and the handling of contaminated reservoir problems. Â